Genetic Polymorphism of Geranylgeranyl Diphosphate Synthase (GGSP1) Predicts Bone Density Response to Bisphosphonate Therapy in Korean Women - Choi, Hyung Jin; Choi, Ji Yeob; Cho, Sun Wook; Kang, Daehee; Han, Ki Ok; Kim, Sang Wan; Kim, Seong Yeon; Chung, Yoon-Sok; Shin, Chan Soo (Yonsei medical journal, 2010)
Genetic factor is an important predisposing element influencing the susceptibility to osteoporosis and related complications. The purpose of the present study is to investigate whether genetic polymorphisms of farnesyl diphosphate synthase (FDPS) or geranylgeranyl diphosphate synthase (GGPS) genes were associated with the response to bisphosphonate therapy. In the present study, 144 Korean women with osteoporosis were included. Among 13 genetic polymorphisms found within the FDPS and GGPS1 gene, 4 genetic polymorphisms with frequencies > 5% were selected for further study. Bone mineral density (BMD) response after 1 year treatment of bisphosphonate therapy was analyzed according to the genotypes. Women with 2 deletion allele of GGPS1 -8188A ins/del (rs3840452) had significantly higher femoral neck BMD at baseline compared with those with one or no deletion allele (0.768 +/- 0.127 vs. 0.695 +/- 0.090 respectively; p = 0.041). The response rate of women with 2 deletion allele of GGPS1 -8188A ins/del (28.6%) was significantly lower than the rate of women with one (81.4%) or no deletion allele (75.0%) (p = 0.011). Women with 2 deletion allele of GGPS1 -8188A ins/del had 7-fold higher risk of non-response to bisphosphonate therapy compared with women with other genotypes in GGPS1 -8188 after adjusting for baseline BMD (OR = 7.48; 95% CI = 1.32-42.30; p = 0.023). Other polymorphisms in FDPS or GGPS1 were not associated with lumbar spine BMD or femoral neck BMD. Our study suggested that GGPS1 -8188A ins/del polymorphism may confer susceptibility to femoral neck BMD response to bisphosphonate therapy in Korean women. However, further study should be done to confirm the results in a larger population.